Quantifying tactile properties of liver tissue, silicone elastomers, and a 3D printed polymer for manufacturing realistic organ models. (April 2020) - Estermann, Sarah-Jane; Pahr, Dieter H.; Reisinger, Andreas
Abstract: In order to produce anatomical models that feel realistic to the touch, artificial materials need to be found that mimic tactile properties of biological tissues. The aim of this study was to provide a guideline for identifying materials that feel similar to biological tissues, based on a quantifiable and reproducible measure. For this, a testing procedure was developed to identify mechanical properties that contribute to tactility. Bovine and porcine liver tissues were compared to different silicone elastomers and a soft 3D printed polymer. Macroindentation was chosen to simulate the palpation of material cubes with loading occurring during actual finger and material interaction. Elastic behaviour was considered by conducting quasistatic loading and unloading for extracting contact stiffness S and equivalent spring stiffness k . Viscoelasticity was quantified by means of force relaxation for calculating loss tangent tan δ based on a Prony series approach. Furthermore, Shore 00 hardness H was measured with a hand-held durometer. For assessing how well materials mimicked liver in terms of tactile properties, a mean error of all measured properties was introduced, referred to as tactile similarity error Q . The 3D printed polymer exhibited the highest error ( Q = 100 − 150 % ), while the material with the lowest error – thus representing liver best – was a super-soft silicone elastomer (nominal hardness of 30 Shore Units) with Q 50 % . In conclusion, a suitable material was found that best represented liver. However, the relatively high tactile similarity error, even for the best material tested, indicates that there is still room for improvement concerning material choice.